TEORI VISUAL KISAH AL-QUR’AN PERSPEKTIF PSIKOLOGI - Hari Bima Laksono; Faishal Khair (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract Interpretation of the Qur'an encompasses various methods and branches, depending on the study's requirements and the type of verse being interpreted. Each method offers a different and complementary perspective of analysis. One such method is the visualisation of the Qur'an, which involves interpreting the Qur'an through imaginary projections. This model of interpretation, also known as 'at-tashwir', was introduced by Sayyid Quthb. This method tries to strengthen the analysis with a visual point of view and then discuss it with psychological studies. The author poses two main questions: What is the visualisation of Qur'anic verses? And how does it correlate with psychological theories? The study will explore the meaning of verses in the Qur'an by emphasising the visual aspects present in the text. Visualisation is based on information that can be perceived by the five human senses: touch, sight, hearing, smell and taste. After obtaining the images, the data will be analysed psychologically, supported by other scientific disciplines such as biology, history, and the arts. The use of psychology and related disciplines' theories will aid in understanding the visualisation. The analysis aims to explore the workings of the five senses and the human body's response to different stimuli. The study found that visualising Qur'anic verses has a significant emotional impact on the reader. The human psyche is closely linked to physical and empirical realities, which mutually influence each other. Keywords: Qur'an, Visualisation, Senses, Imagination, Psychology